The Influence of Auditory, Intellectually, Repetition (AIR) Learning Models on Learning Motivation of 5th Class Students in IPS Courses - Dewi Ayuhani; Septiyati Purwandari; Kun Hisnan Hajron (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
The purpose of this study was to determine how the influence of the Auditory, Intellectually, Repetition learning model can increase the learning motivation of grade 5 students in social studies subjects at MI Muhammadiyah Salafiyah Bandongan. The method used in this study is a pre-experiment using a one-group pretest-posttest design. The population and sample of this study used a sample of 15 students of class 5 MI Muhammadiyah Salafiyah Bandongan. The analysis used was an independent t-test analysis using the SPSS 25.00 program for windows. Based on the results of research and discussion, it can be concluded that there is an effect of using the AIR learning model on the motivation to learn social studies subjects in class V MI Muhammadiyah Salafiyah Bandongan. This is evidenced by the average score on the pre-test training questions is 60.27 with the highest score of 72 and the lowest score of 48. While the average value of the post-test training questions is 81.07 with the highest score of 92 and the lowest score of 68. This result is strengthened by the calculation of the